Studi tentang BMB3 (Berpikir, Merasa, Bersikap, Bertindak, dan Bertanggung jawab) Siswa Berkenaan dengan Perilaku Bullying - Mustika Utari; Afrizal Sano (Jurnal Neo Konseling, 2019)
This research is based on the phenomenon found in the field related to bullying behavior. The purpose of this study is to describe BMB3 (Berpikir, Merasa, Bersikap, Bertindak, and Bertanggung jawab) students regarding bullying behavior. This research is descriptive, with a sample of students of class XI and XII at SMAN 7 Padang, totaling 252 students. The research instrument used was a Likert scale. The data obtained were analyzed using percentage techniques. The research findings reveal the study of student BMB3 with regard to bullying behavior can be seen from aspects: (1) students' thinking regarding bullying behavior is in a very good category; (2) feel that students regarding bullying behavior are in a good category; (3) the attitude of students regarding bullying behavior is in the good category; (4) acting students in relation to bullying behavior are in the good category; (5) responsible students in relation to bullying behavior are in a very good category. From the results of these findings as a whole it can be concluded that the study of student BMB3 with regard to bullying behavior is in the good category.